Evaluation of Protracted Cisplatinum Infusion in Advanced Anaplastic Thyroid Cancer - Gopa Ghosh; O.P. Singh (International Journal of Medical Research and Review, 2013)
Introduction: Anaplastic thyroid cancer (ATC) constitutes 1-3% of all thyroid malignancies. Most of the patients of anaplastic thyroid cancer presents with advanced inoperable lesion associated with neck mass dysphagia, and SVC syndrome. At this stage only treatment that can be offered is chemotherapy, as this variety of thyroid cancer does not generally concentrate iodine. Present study evaluates protracted (8 hr) Cisplatinum (CDDP) infusion along with doxorubucin in comparison to conventional (1hr) Cisplatinum + doxorubucin in advanced anaplastic thyroid cancer in terms of tolerance, toxicities and response rates.Methods: 32 previously untreated cases of stage III/IV inoperable anaplastic thyroid cancer were included in the present study. Patients were divided into 2 arms of 16 patients each. Arm I (16 patients) received 1 hr Cisplatin (CDDP) infusion 75mg/m2 + Doxorubicin 60mg/m2 infusion & Arm II (16 patients) received protracted 8 hrs CDDP infusion 75mg/m2+ Doxorubicin 60mg/m2 infusion. All patients were evaluated for tolerance, toxicities and response rate.Results: Arm II patients showed better locoregional response with CR 31.25%, PR 50%, SD 6.25%,PrD. 12.5% as compared to Arm I patients with CR 12.5%, PR 43.75%, SD 18.75%, Pr. D 25%, p= .02. Toxicities like mucositis, nausea & vomiting, diarrhea, nephrotoxicity were also significantly less in Arm II. After completion of 3-4cycles of Induction CT, all patients were treated with External Radiotherapy of 60-66Gy, followed with 2-3 cycles of adjuvant CT.Conclusion: From the present study it can be concluded that protracted cisplatinum infusion along with other chemotherapeutic drugs is an effective and acceptable CT regimen in advanced inoperable thyroid cancer.